2003
DOI: 10.1152/ajpendo.00397.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hypercortisolemia alters muscle protein anabolism following ingestion of essential amino acids

Abstract: Debilitating injury is accompanied by hypercortisolemia, muscle wasting, and disruption of the normal anabolic response to food. We sought to determine whether acute hypercortisolemia alters muscle protein metabolism following ingestion of a potent anabolic stimulus: essential amino acids (EAA). A 27-h infusion (80 μg · kg−1 · h−1) of hydrocortisone sodium succinate mimicked cortisol (C) levels accompanying severe injury (>30 μg/dl), (C + AA; n = 6). The control group (AA) received intravenous saline ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…2 H5]phenylalanine was added to the EAA drink to maintain the isotopic enrichment (tracer-to-tracee ratio) in the femoral artery at ϳ0.08 (30). The amino acids were dissolved in 250 ml of a noncaloric, noncaffeinated soft drink and consumed as a bolus at 1100.…”
Section: L-[ring-mentioning
confidence: 99%
See 1 more Smart Citation
“…2 H5]phenylalanine was added to the EAA drink to maintain the isotopic enrichment (tracer-to-tracee ratio) in the femoral artery at ϳ0.08 (30). The amino acids were dissolved in 250 ml of a noncaloric, noncaffeinated soft drink and consumed as a bolus at 1100.…”
Section: L-[ring-mentioning
confidence: 99%
“…It is possible that detecting age-related differences in postabsorptive protein metabolism is beyond the sensitivity limits of current technology. However, after ingestion of amino acids, the supply of the precursor elements necessary to stimulate protein synthesis can increase substantially, albeit transiently (30). Consequently, it is perhaps more likely that any age-related alteration in muscle protein synthesis and/or breakdown will be exaggerated during the period immediately after nutrient ingestion and may therefore be more readily detectable.…”
mentioning
confidence: 99%
“…We have previously demonstrated that EAA supplementation effectively stimulates net muscle protein synthesis acutely (24) and after 28 d of BR (23). Furthermore, as little as 15 g of EAAs can stimulate muscle protein synthesis and maintain net protein balance for more than 90 min in the presence of acute hypercortisolemia (Ͼ30 g⅐dl Ϫ1 ) (25). The goal of the current study was to expand on our previous research and examine the combined effects of prolonged BR and acute hypercortisolemic challenges, a model depicting two common consequences of hospitalization due to trauma or illness.…”
mentioning
confidence: 99%
“…Lack of a decrease in protein catabolism, despite an increase in plasma insulin and abundant amino acid supply during HDϩAA, could be due to a concomitant increase in plasma cortisol (37) and proinflammatory cytokine activation (19). Preliminary evidence from our laboratory has shown that IL-6 is released from skeletal muscle (41) and may mediate muscle protein catabolism (42,43).…”
Section: Discussionmentioning
confidence: 95%
“…Sham HD has been shown to induce muscle protein catabolism even in the absence of amino acid loss (23). Augmented protein catabolism that is uncorrected by amino acid infusion could be due to concomitant increase in plasma cortisol (37) and cytokine activation (19,44); both are known to induce protein catabolism. Similar changes in protein kinetics are observed in other stress states (4,16).…”
Section: Discussionmentioning
confidence: 99%